2023
DOI: 10.1212/wnl.0000000000206758
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Developmental and Epileptic Encephalopathy and of Intellectual Disability and Epilepsy in Children

Abstract: Background and Objectives:We aimed to determine the population-based cumulative incidence and prevalence of developmental and epileptic encephalopathies (DEEs) and intellectual disability and epilepsy (ID+E) in children. We analyzed the cumulative incidence of specific epilepsy syndromes.Methods:Children under 16 years with a DEE or ID+E were ascertained using EEG records from 2000-2016 in the Wellington region of New Zealand. Epilepsy syndromes were diagnosed on medical record and EEG review. Point prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…By virtue of a median clinical follow-up period of about 8 years, the authors also studied features including seizure-freedom rates, progression from epileptic spasms (ES) to other syndromes, differing severities of ID in patients with DEE and in children with IDþE, deaths, and the number of resolved epilepsy cases. 1 The authors found that the cumulative incidence of the combination of DEE and IDþE before age 16 years was quite large: 1 in 340 children. 1 Specifically, the incidence of DEE was 1 in 590 children through childhood and adolescence, which is more than double the incidence found in a Scottish study of DEE with onset before age 3 years.…”
Section: Commentarymentioning
confidence: 99%
See 3 more Smart Citations
“…By virtue of a median clinical follow-up period of about 8 years, the authors also studied features including seizure-freedom rates, progression from epileptic spasms (ES) to other syndromes, differing severities of ID in patients with DEE and in children with IDþE, deaths, and the number of resolved epilepsy cases. 1 The authors found that the cumulative incidence of the combination of DEE and IDþE before age 16 years was quite large: 1 in 340 children. 1 Specifically, the incidence of DEE was 1 in 590 children through childhood and adolescence, which is more than double the incidence found in a Scottish study of DEE with onset before age 3 years.…”
Section: Commentarymentioning
confidence: 99%
“…1 The authors found that the cumulative incidence of the combination of DEE and IDþE before age 16 years was quite large: 1 in 340 children. 1 Specifically, the incidence of DEE was 1 in 590 children through childhood and adolescence, which is more than double the incidence found in a Scottish study of DEE with onset before age 3 years. 2 The cumulative incidence of IDþE was 1 in 800 children, and 70% of the latter cases had epilepsy onset between ages 3 and 15 years.…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations
“…The developmental and epileptic encephalopathies (DEEs) are the most severe group of epilepsies, defined by frequent epileptiform activity associated with developmental slowing or regression 1 . While each genetic etiology is rare, with more than 825 genes implicated 2 , the cumulative incidence of DEEs overall is 1 in 590 children 3 . Currently, de novo, X-linked, or recessively inherited pathogenic germline variants are found in ∼50% of individuals with DEEs who undergo genetic testing 4 .…”
Section: Introductionmentioning
confidence: 99%